Using in vivo animal models for studying SARS-CoV-2. (1st February 2022) - Da Costa, Camila B. P.; Cruz, Ana Claudia De Menezes; Penha, Julio Cesar Q; Castro, Helena C; Da Cunha, Luis E. R.; Ratcliffe, Norman A; Cisne, Rafael; Martins, Francislene Juliana
ABSTRACT: Introduction: The search for an animal model capable of reproducing the physiopathology of the COVID-19, and also suitable for evaluating the efficacy and safety of new drugs has become a challenge for many researchers. Areas covered: This work reviews the current animal models for in vivo tests with SARS-CoV-2 as well as the challenges involved in the safety and efficacy trials. Expert opinion: Studies have reported the use of nonhuman primates, ferrets, mice, Syrian hamsters, lagomorphs, mink, and zebrafish in experiments that aimed to understand the course of COVID-19 or test vaccines and other drugs. In contrast, the assays with animal hyperimmune sera have only been used in in vitro assays. Finding an animal that faithfully reproduces all the characteristics of the disease in humans is difficult. Some models may be more complex to work with, such as monkeys, or require genetic manipulation so that they can express the human ACE2 receptor, as in the case of mice. Although some models are more promising, possibly the use of more than one animal model represents the best scenario. Therefore, further studies are needed to establish an ideal animal model to help in the development of other treatment strategies besides vaccines.